2022
DOI: 10.3389/fgene.2022.933798
|View full text |Cite
|
Sign up to set email alerts
|

A novel ten-gene prognostic signature for cervical cancer based on CD79B-related immunomodulators

Abstract: The identification of immune-related prognostic biomarkers opens up the possibility of developing new immunotherapy strategies against tumors. In this study, we investigated immune-related biomarkers in the tumor microenvironment to predict the prognosis of cervical cancer (CC) patients. ESTIMATE and CIBERSORT algorithms were used to calculate the abundance of tumor-infiltrating immune cells (TICs) and the amount of immune and stromal components in cervical samples (n = 309) from The Cancer Genome Atlas. Ten i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Other studies have focused on analyzing genes involved in ubiquitination, whose role in CC has yet to be determined. (80) reported an immune signature composed of 10 genes: CD96, LAG3, PDCD1, TIGIT, CD27, KLRK1, LTA, PVR, TNFRSF13C, and TNFRSF17; these genes are CD79B associated immunomodulators, that showed an independent prognostic value. A study that analyzed RNAseq databases of genes related to the glycosylation process (glycogens) showed that adenocarcinoma tumors displayed a unique glycogen expression signature.…”
Section: New Advances In Molecular Characterization Of Cervical Cancermentioning
confidence: 99%
“…Other studies have focused on analyzing genes involved in ubiquitination, whose role in CC has yet to be determined. (80) reported an immune signature composed of 10 genes: CD96, LAG3, PDCD1, TIGIT, CD27, KLRK1, LTA, PVR, TNFRSF13C, and TNFRSF17; these genes are CD79B associated immunomodulators, that showed an independent prognostic value. A study that analyzed RNAseq databases of genes related to the glycosylation process (glycogens) showed that adenocarcinoma tumors displayed a unique glycogen expression signature.…”
Section: New Advances In Molecular Characterization Of Cervical Cancermentioning
confidence: 99%